Description of the female of Simulium (Gomphostilbia) aziruni (Diptera: Simuliidae) and its genetic relationships with members of the Simulium gombakense species-group - Ya'cob, Zubaidah; Takaoka, Hiroyuki; Low, Van Lun; Tan, Tiong Kai; Sofian-Azirun, Mohd (Elsevier, 2019)
Simulium (Gomphostilbia) aziruni Takaoka, Hashim & Chen was described initially based only on a pupa and a mature larva collected from Peninsular Malaysia. Herein, we describe the morphological characters of the female of S. aziruni for the first time. It resembles those of the other members of the Simulium gombakense species-group by the genital fork with a distinct projection directed medioposteriorly from each arm and claw with a large basal tooth. Cytochrome c oxidase I (COI) barcoding analysis indicates that S. aziruni is the sister species of S. maleewongae, but both are distantly separated by a genetic distance of 4.9%. © 2019 Elsevier B.V.